The oldest fossil darkling beetle of the genus Neomida Latreille, 1829 (Coleoptera: Tenebrionidae) from Eocene Baltic amber examined with X-ray microtomography - Nabozhenko, Maxim V.; Kairišs, Kristaps; Bukejs, Andris (Zootaxa, 2020)
Based on a single well-preserved specimen from Eocene Baltic amber, a new tenebrionid beetle Neomida groehni Nabozhenko et Bukejs sp. nov. (Diaperinae: Diaperini) is described and illustrated using phase-contrast X-ray microtomography. This oldest representative of the genus differs from all known extant and extinct congeners by the dorsally very weakly convex pronotum with undulate lateral margins (while other Neomida have a pronotum that is strongly convex along its transverse axis, with evenly rounded lateral margins); distinct, right posterior angles of pronotum; and elevated sutural area of the elytra.